2023
DOI: 10.3390/nu15061318
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Frequency of Positive and Negative Effects after Acute Caffeine Consumption

Abstract: Gender-specific caffeine-related adverse effects should be thoroughly investigated. Sixty-five adult participants were included in the study, 30 men and 35 women (age, 22.5 ± 2.8; body weight, 71.7 ± 16.2 kg; BMI, 23.6 ± 4.4). The participants who were classified as low and moderate caffeine users received 3 mg/kg, and high caffeine users received 6 mg/kg of caffeine in one dose. One hour after ingestion of caffeine and within twenty-four hours, the participants completed a side effect questionnaire. Effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Interestingly, females reported greater effects following the consumption of decaffeinated beverage [ 105 ]. Domaszewski et al [ 106 ] reported an increased occurrence of self-reported positive effects of caffeine in males compared to females. Positive and negative effects were assessed via the “Negative and Positive Effects after Caffeine Ingestion Questionnaire (QUEST).” A study evaluating cognitive performance via mental calculations reported that both sexes improved performance with no significant differences between females and males [ 102 ].…”
Section: Are There Sex Differences Regarding Caffeine’s Effects?mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, females reported greater effects following the consumption of decaffeinated beverage [ 105 ]. Domaszewski et al [ 106 ] reported an increased occurrence of self-reported positive effects of caffeine in males compared to females. Positive and negative effects were assessed via the “Negative and Positive Effects after Caffeine Ingestion Questionnaire (QUEST).” A study evaluating cognitive performance via mental calculations reported that both sexes improved performance with no significant differences between females and males [ 102 ].…”
Section: Are There Sex Differences Regarding Caffeine’s Effects?mentioning
confidence: 99%
“…Likewise, caffeine’s effects on sports performance are mixed. Caffeine is an ergogenic aid, and even the placebo effect of caffeine improves sports performance irrespective of sex, with some studies reporting greater performance advantages in males [ 102 , 106–108 ].…”
Section: Are There Sex Differences Regarding Caffeine’s Effects?mentioning
confidence: 99%
“…Caution should remain in considering males and females as a homogenous group due to the observed differences in physiology and hormones that could potentially influence processes of absorption and metabolism 6 , 10 . Indeed, there is evidence to suggest differences in the ergogenic effect of CAF on performance across different sports 11 and the occurrence of negative psychological disposition 12 between males and females, albeit this has not been observed consistently 13 , 14 . Although the precise process causing the various reactions to the supplement is not yet understood, body composition and size may be among the influencing factors 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is evidence to suggest differences in the ergogenic effect of CAF on performance across different sports 11 and the occurrence of negative psychological disposition 12 between males and females, albeit this has not been observed consistently 13 , 14 . Although the precise process causing the various reactions to the supplement is not yet understood, body composition and size may be among the influencing factors 12 . Specifically, CAF is mainly distributed through free body mass 15 , The larger percentage of adipose tissue may lead to higher CAF concentrations in the tissue and plasma 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, restlessness, nervousness, and gastric pain have been observed with caffeine intoxication [ 9 , 10 ]. The effects of coffee and caffeinated beverages depend on individual characteristics, such as body weight, gender, physiological condition, and the dose consumed [ 11 ]. Nevertheless, no study has demonstrated the beneficial or harmful effects on children.…”
Section: Introductionmentioning
confidence: 99%